2022
DOI: 10.3991/ijim.v16i15.31695
|View full text |Cite
|
Sign up to set email alerts
|

Application of Augmented Reality in Teaching and Learning in Engineering Programs

Abstract: Augmented reality is one of the new emerging technologies in the world, since its appearance was considered for many years its application in education as a tool in the student's learning process. Taking these aspects into account, the present research article was developed, which is based on the design proposal using augmented reality in the learning process at a university in northern Lima. In which the analysis, architecture and development of a prototype was showed in detail. The result of the article was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This result is similar to previous studies where the average effect size of studies on the influence of AR use in education is in the range of 0.6 to 0.8 (e.g., [4], [26]). This study also supports previous studies that state that integrating AR in educational environments helps improve students' academic achievement in collaborative learning environments and increases their retention and ability to translate it into other environments [13]- [15]. The analytical results also prove the superiority of the experimental group in general, not only in terms of cognitive but also in terms of student motivation (e.g., [46], [47]), cognitive development [48], student collaboration [49], and their learning experiences [50], [51].…”
Section: Fig 2 Research Funnel Plotsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to previous studies where the average effect size of studies on the influence of AR use in education is in the range of 0.6 to 0.8 (e.g., [4], [26]). This study also supports previous studies that state that integrating AR in educational environments helps improve students' academic achievement in collaborative learning environments and increases their retention and ability to translate it into other environments [13]- [15]. The analytical results also prove the superiority of the experimental group in general, not only in terms of cognitive but also in terms of student motivation (e.g., [46], [47]), cognitive development [48], student collaboration [49], and their learning experiences [50], [51].…”
Section: Fig 2 Research Funnel Plotsupporting
confidence: 90%
“…However, various previous empirical studies have provided varying and inconsistent results. Several studies have found that AR-based learning can increase students' interest in learning, thereby supporting the improvement of their academic abilities (e.g., [13]- [17]). In contrast, several other individual studies show different results that the use of AR has no or only a small impact on students' abilities (e.g., [18], [19]).…”
Section: Introductionmentioning
confidence: 99%
“…Thornton and Lammi (2021) Qualitative: They determined as results of their research that some students, although they were unaware of AR technology, there is great interest in the use of this technology in their learning process; in this way students, teachers and the university institution benefit. Silva et al (2022) Based on the results obtained in Figure 4, a model is shown in which it is possible to categorise the results obtained based on the research questions, the same ones that focused on identifying the areas or specialties in which AR were applied, as well as the techniques used and forms of activation or triggering of the AR application, and finally the factors analysed that evidenced the contribution of augmented reality in the learning of engineering students. In this way, in the model presented, the starting point is augmented reality, and that, when applied to different areas or specialties, relying on activation or firing techniques and elements, results in the categorisation of three contribution groups on the students of engineering in the field of virtual teaching and learning in the midst of COVID-19.…”
Section: Tuli Et Al (2022)mentioning
confidence: 99%
“…Piaget's theory of cognitive conflict emphasizes that knowledge development occurs through the process of achieving balance. According to Piaget, imbalance is the main catalyst for knowledge development, and he encourages students to experiment in order to achieve a new balance by assimilating knowledge [28]. The cognitive conflict strategy is implemented through steps in which the student is asked about a specific concept, and their answer is then received and interpreted individually [29].…”
Section: Cognitive Conflict Strategiesmentioning
confidence: 99%